2019
DOI: 10.1128/jb.00511-19
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite Regulation of the glpFKD Operon Involved in Glycerol Catabolism by GylR, Crp, and SigF in Mycobacterium smegmatis

Abstract: The glpD (MSMEG_6761) gene encoding glycerol-3-phosphate dehydrogenase was shown to be crucial for M. smegmatis to utilize glycerol as the sole carbon source. The glpD gene likely forms the glpFKD operon together with glpF and glpK, encoding a glycerol facilitator and glycerol kinase, respectively. The gylR (MSMEG_6757) gene, whose product belongs to the IclR family of transcriptional regulators, was identified 182 bp upstream of glpF. It was demonstrated that GylR serves as a transcriptional activator and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…We found high GlpK activity in glycerol-grown Msm cells and induced expression from the glpFKD operon that codes for the glycerol utilizing enzymes, including GlpK. We expected that glycerol would induce expression of the genes belonging to the glpFKD operon as in an earlier study [21]; the authors had demonstrated using reporter assays that this operon’s promoter is glycerol inducible. But the novel observation that we have made here is that Fbp activity increases significantly during growth in glycerol.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…We found high GlpK activity in glycerol-grown Msm cells and induced expression from the glpFKD operon that codes for the glycerol utilizing enzymes, including GlpK. We expected that glycerol would induce expression of the genes belonging to the glpFKD operon as in an earlier study [21]; the authors had demonstrated using reporter assays that this operon’s promoter is glycerol inducible. But the novel observation that we have made here is that Fbp activity increases significantly during growth in glycerol.…”
Section: Discussionmentioning
confidence: 59%
“…The genes that code for the glycerol utilizing enzymes, glpK (glycerol kinase), glpD (glycerol-3-phosphate dehydrogenase), and glpF (glycerol uptake facilitator), are organized in an operon, the glpFKD operon. The operon's expression is controlled in a tripartite manner by GlpR, the operon regulator, cyclic AMP receptor protein (Crp), and SigF [21]. We sought to investigate the expression of the genes encoded by the glpFKD operon using qRT-PCR assays.…”
Section: Induction Of Gene Expression By Glucose and Glycerolmentioning
confidence: 99%
“…For Huc production, protein expression was performed using the M. smegmatis mc 2 155 strain PRC1, which lacks the glycerol response regulator gylR (gylR Leu154->Frameshift) and the Hhy hydrogenase (hhyS inactivation) [33, 75]. To facilitate Huc purification, a 2×StrepII tag was inserted at the N-terminal end of the small subunit (MSMEG_2262, HucS) through allelic exchange mutagenesis as described previously [76].…”
Section: Methodsmentioning
confidence: 99%
“…Thus it can be seen that glycerol can serve as a common precursor to biosynthesize various products. Usually, the genes encoding the enzymes for conversion of glycerol to DHAP are tightly controlled by different types of transcriptional regulators (Lin, 1976;Hindle and Smith, 1994;Bong et al, 2019;Poblete-Castro et al, 2020). Understanding the molecular regulatory mechanism of glycerol metabolism is critical for better use of glycerol to produce valuable products.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies have revealed that the expression of glp operon can be induced by the addition of glycerol during fermentation (Baños et al, 2009;Guo et al, 2013). Studies in non-Streptomyces strains, such as Mycolicibacterium smegmatis (previously known as Mycobacterium smegmatis), indicated that G3P rather than glycerol might bind to GylR-like proteins, and, as a result, regulate the glp operon (Bong et al, 2019). Despite the aforementioned studies, the exact binding sequences and the small molecule effectors of GylR-like proteins remain elusive in Streptomyces.…”
Section: Introductionmentioning
confidence: 99%